2011
DOI: 10.1177/0165025411398182
|View full text |Cite
|
Sign up to set email alerts
|

Parents as role models: Parental behavior affects adolescents’ plans for work involvement

Abstract: This study (N ¼ 520 high-school students) investigates the influence of parental work involvement on adolescents' own plans regarding their future work involvement. As expected, adolescents' perceptions of parental work behavior affected their plans for own work involvement. Same-sex parents served as main role models for the adolescents' own plans, whereas opposite-sex parents served as models for the preferred degree of work participation for the adolescents' future life partners. Interestingly, ideals of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 13 publications
5
36
0
Order By: Relevance
“…This implies that, adolescents are more likely to adopt the behaviors of their parents concerning handling social challenges. The findings agree with a study carried out by Wiese and Alexandra (2011 ) which reported that young people learn a lot from their parents as role models, although they may reflect and modify these models according to their beliefs and social relations. This is supported by the study by Karen (2007) who argues that, Table 5.0 shows responses from guidance and counseling teachers on drug related cases, majority (67%) of the schools recording up to 10 cases per school term of three months and others (13%) recording up to over 30 cases per term.…”
Section: Tabl-4 Students' Expectation Of Their Parentssupporting
confidence: 91%
“…This implies that, adolescents are more likely to adopt the behaviors of their parents concerning handling social challenges. The findings agree with a study carried out by Wiese and Alexandra (2011 ) which reported that young people learn a lot from their parents as role models, although they may reflect and modify these models according to their beliefs and social relations. This is supported by the study by Karen (2007) who argues that, Table 5.0 shows responses from guidance and counseling teachers on drug related cases, majority (67%) of the schools recording up to 10 cases per school term of three months and others (13%) recording up to over 30 cases per term.…”
Section: Tabl-4 Students' Expectation Of Their Parentssupporting
confidence: 91%
“…It is important to note that, parental supervision is paramount whether the child is living with other siblings or is the only child. These findings supported the claim made by [26] in their study on birth order and adolescent delinquent behaviour. They found out that first born children were less involved in delinquency than middle born children.…”
Section: Parental Supervisionsupporting
confidence: 90%
“…These children are usually frustrated in school and they end up performing poorly in academics and interpersonal relationships. [26] in their study introduced a new concept by claiming that while parental involvement was important towards student's behaviour, it differs from family to family, depending on the level of marginalization. For instance, students who come from rich families can be affected by parents not spending time with them; the same does not apply to the poorer families (Rangarajan & Kelly, 2006).…”
Section: Sharing Problems With the Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our hypothesis is consistent with social learning theory (Bandura, ), which emphasizes the centrality of the concept of modeling for understanding the socialization process. Therefore, parents can have an effect in shaping adolescents’ SCC acting as modeling agents (Wiese & Freund, ). In fact, parents with self‐beliefs that are clearly and confidently defined, internally consistent, and temporally stable might represent for adolescents—who are searching for their identity—a more attractive model than parents with less clear self‐beliefs.…”
Section: Self‐concept Clarity: What Is It and Why Does It Matter?mentioning
confidence: 99%